Bilateral, Solitary, Extramacular Vitelliform Retinal Lesions in a Patient With Best Disease. (November 2020) - Duker, Jacob; Patel, Nimesh A.; Yannuzzi, Nicolas A.; Prakhunhungsit, Supalert; Negron, Catherin I.; Berrocal, Audina M.
Purpose: This work describes the first published case of Best vitelliform macular dystrophy (BVMD) with bilateral, solitary, extramacular retinal lesions. Methods: A case report is presented. Results: An 8-year-old girl with a family history of BVMD was referred for suspicious peripheral retinal lesions. Multimodal imaging disclosed bilateral, solitary, extramacular lesions consistent with the vitelliform lesions found in BVMD. There were no abnormalities in the macula. Conclusions: This is the first documented case of solitary, bilateral, extramacular vitelliform lesions in BVMD.